2018
DOI: 10.26644/em.2018.013
|View full text |Cite
|
Sign up to set email alerts
|

Golf and Skin Health: A Narrative Review

Abstract: History: Objectives: Recent studies have reported that playing golf has overall physical and mental health benefits. Through being placed in the sun for extended periods of time, the golfing population faces an increased risk of ultraviolet radiation (UVR) associated skin problems, most importantly skin cancer. Our aim was to collate and summarise current literature on the relationship between golf and skin cancer. Methods: We searched multiple web-based, health-focused databases (Medline, Embase, Cinahl, Web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The scoping review,19 spectator health study,20 international consensus on golf and health22 and associated studies23–29 were all published open access following peer-review, with six publications in the British Journal of Sports Medicine , which has the strongest 2019 impact factor (11.6) in the field, whose website achieves >8 million hits per year, and has >200 000 followers of their social medias.…”
Section: Resultsmentioning
confidence: 99%
“…The scoping review,19 spectator health study,20 international consensus on golf and health22 and associated studies23–29 were all published open access following peer-review, with six publications in the British Journal of Sports Medicine , which has the strongest 2019 impact factor (11.6) in the field, whose website achieves >8 million hits per year, and has >200 000 followers of their social medias.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of this analysis have key implications for golf participants with regard to sun protection practices. Matthews et al ’s29 recent narrative review concluded that while definitive evidence exists to indicate that golf participants are exposed to potentially harmful levels of UVR during play, epidemiological studies are required to understand more about the risks to skin health that golf participants face from this exposure. Although causation cannot be established from our study, the findings provide greater insight into morbidity related to sun exposure for golf participants than previous studies in this field have provided to date.…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence regarding the physical health benefits and well-being of playing golf has been clearly outlined in the literature, [9][10][11][12] the evidence related to the benefits of VI golf is still limited. This study is unique in identifying not only the health and mental health benefits but also the psychosocial benefits due to the socialization opportunities VI golf creates.…”
Section: The Perspectives Of VI Golfers and Guides On Vi Golfmentioning
confidence: 99%
“…Playing golf has been shown to have a positive impact on the health and well-being of the general population 9–12 and is a sport very suited to people with different types of impairment. Golf is not yet as popular among disabled people as it is among their nondisabled counterparts 7 and has high dropout rates and a small transition rate into regular participation 13–15 .…”
mentioning
confidence: 99%